Language Disorders in Children with Unilateral Hearing Loss: A Systematic Review - José, Maria Renata; Mondelli, Maria Fernanda Capoani Garcia; Feniman, Mariza Ribeiro; Lopes-Herrera, Simone Aparecida (International Archives of Otorhinolaryngology, 2014)
Introduction Childhood is a critical period for language development and maturation of the central auditory system. Unilateral hearing loss (UHL) is considered a minimal impairment, and little is discussed regarding its impact on the development of language, communication, and school performance.Objectives A bibliographical survey of scientific articles published from 2001 to 2011 was performed to verify which language disorders can occur in children with UHL and which tests were performed to identify them.Data Synthesis Three databases were used: PubMed, Lilacs, and The Cochrane Library. As inclusion criteria, the articles should have samples of children with UHL, without other impairments, aged between 3 months and 12 years, and reference to language tests applied in this population. Out of 236 papers initially selected, only 5 met the inclusion criteria. In the articles studied, 12 tests were used for language assessment in children with UHL, out of which 9 were directed toward expressive language, and 3 toward receptive language. Children with UHL demonstrated lower scores on receptive and expressive language tests when compared with children with normal hearing. However, they obtained better scores on expressive language tests than children with bilateral hearing loss.Conclusion The findings of this survey showed that only a small number of studies used language tests in children with UHL or addressed language alterations resulting from this type of impairment. Therefore we emphasize the importance of investments in new studies on this subject to provide better explanations related to language difficulties presented by children with UHL.
Keywords: hearing loss; unilateral; child; language development; language